(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, the importance of raising the worldview of children from a young age with help of Proverbs is reflected. The proverbs are given as an analysis of the role of children in maturation.